High Patient Disease Burden in a Cross-sectional, Multicenter Contact Registry Study of Eosinophilic Gastrointestinal Diseases. Issue 4 (October 2020) - Jensen, Elizabeth T.; Aceves, Seema S.; Bonis, Peter A.; Bray, Kimberly; Book, Wendy; Chehade, Mirna; Collins, Margaret H.; Dellon, Evan S.; Falk, Gary W.; Gonsalves, Nirmala; Gupta, Sandeep K.; Hirano, Ikuo; et al.
ABSTRACT: Objectives: Clinical features of eosinophilic esophagitis (EoE) have been well-described in the literature, however, characterization of features experienced by patients with other eosinophilic gastrointestinal diseases (EGIDs) is lacking. Using data collected from a patient contact registry, we sought to characterize and contrast patient-reported gastrointestinal and extragastrointestinal symptoms and comorbidities in non-EoE EGIDs, including eosinophilic gastritis, gastroenteritis and colitis, relative to EoE. Methods: We conducted a cross-sectional study of contact registry data collected from 2015 to 2018. Statistical comparisons were made using chi-square (categorical measures) and the Mann-Whitney U test (continuous measures). Multivariable analyses were used to evaluate associations between treatment and feelings of isolation. Results: Of the 715 reporting an EGID diagnosis (n = 525 EoE; n = 190 non-EoE EGID), a higher proportion of those with a non-EoE EGID reported more frequent specific and nonspecific gastrointestinal symptoms, including nausea, abdominal pain, diarrhea, constipation, and bloating ( P < 0.01 for all). Participants with a non-EoE EGID were more likely to report higher frequency of fatigue, isolation, and deep muscle or joint pain ( P < 0.01 for all). Specific food elimination and elemental formula treatments were associated with increased odds of more frequent (at least weekly) feelings of isolation for participants with EoE (adjusted odds rtaio [aOR]: 2.4; 95% confidence interval [CI]: 1.5–4.1 for specific food elimination and adjusted OR: 1.9; 95% CI: 1.2–3.3 for elemental formula). Conclusions: Significant differences exist in the symptoms and comorbidities experienced between those with EoE versus non-EoE EGIDs. Additional investigation is needed to elucidate the factors that may contribute to the high disease burden of these poorly understood conditions. Abstract : Supplemental Digital Content is available in the text